The role of miRNA in motor neuron disease - Kye, Min Jeong; Gonçalves, Inês do Carmo G. (Frontiers in Cellular Neuroscience, 2014)
microRNA is a subset of endogenous non-coding RNA. It binds to partially complementary sequences in mRNAs and inhibits mRNA translation by either blocking translational machinery or degrading mRNAs. It is involved in various cellular processes including cell cycle, development, metabolism and synaptic plasticity. Dysregulation of miRNA expression and function is reported in various diseases including cancer, metabolic disorders as well as neurological disorders. In nervous system, miRNA related pathways play a very important role in development and function of neuronal cells. Moreover, numerous evidences suggest that dysregulated miRNA related pathways contribute to pathology of neurological disorders such as Alzheimer’s disease, amyotrophic lateral sclerosis and spinal muscular atrophy. Here, we review current knowledge about the role of miRNAs in motor neuron disorders, especially about two common diseases: spinal muscular atrophy and amyotrophic lateral sclerosis.